Exploring the physical activity levels of egyptian women with premenstrual syndrome: a preliminary study - Mai M. A. Shehata; Dalia M. Kamel; Nisreen A. Helmy; Amir A. Gabr; Shymaa Mohamed Ali; Manal A. El-Shafei (IP Iermakov S.S., 2024)
Background and Study Aim. Premenstrual syndrome (PMS) affects a significant proportion of women, impacting their daily lives and well-being. The association between physical activity levels, the prevalence of premenstrual syndrome (PMS), and the severity of PMS remains debatable. Therefore, this study aimed to identify physical activity levels among a cohort of Egyptian females with PMS. Material and Methods. This study included one hundred females with PMS. Physical activity levels, anaerobic power, aerobic capacity, BMI, and dysmenorrhea were investigated. PMS severity was assessed using the Premenstrual Syndrome Scale (PMSS), and the females' physical activity was evaluated using the International Physical Activity Questionnaire (IPAQ). The 1-mile submaximal test and the Running-Based Anaerobic Sprint Test (RAST) were used to assess aerobic capacity and anaerobic power, respectively. Results. The findings revealed a significant association between PMS severity and physical activity (p < 0.05). There was no significant difference in aerobic capacity among those with mild, moderate, and severe PMS (p > 0.05). There was no significant association between PMS severity and marital status (p > 0.05), whereas there was a significant association with dysmenorrhea (p < 0.05), especially among moderate and severe PMS sufferers. Females with severe PMS had a significantly higher BMI than those with mild PMS (p < 0.05) and those with moderate PMS (p < 0.05). Mild and moderate PMS females showed no significant difference in BMI (p > 0.05). Conclusions. It can be concluded that physical activity levels and BMI may affect PMS. Therefore, being physically active and maintaining a normal-range BMI might reduce PMS severity.